CGIAR Climate Impact Platform launches Dgroups platform in 2024 to convene CGIAR scientists and partners - Rabago, Laura (CGIAR Climate Change Impact Platform, 2024)
The CGIAR Climate Impact Platform has successfully launched the Dgroups platform, creating a dynamic space for CGIAR scientists and partners to engage, collaborate, and share knowledge. Designed as a hub for the Climate Community of Practice, the platform facilitates the exchange of content, resources, and knowledge management products to drive collective learning and innovation. Since its launch, Dgroups has hosted rich discussions, disseminated valuable insights, and strengthened connections among members, fostering a sense of community and shared purpose.